Zur Metapher der Metasprache aus translationswissenschaftlicher Sicht am Beispiel der „Geschichte der neueren Sprachwissenschaft“ von Gerhard Helbig - Paweł Bąk (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
The topic of the article is the conduit metaphor of the metalanguage as a problem of translation. The essay is a continuation of a cycle of studies on the metaphor in meta-linguistic discourses. The Polish translation of Gerhard Helbig's work „Geschichte der neueren Sprachwissenschaft“ (‘The History of Modern Linguistics’) documents similarities in the metaphorics of the German and Polish metalanguages, which confirms the thesis about the congruence of metaphors of Western culture. Theoretical aspects will be discussed that may help in the translation of the metaphor.